METAMORPHIC DESIGN AND DEGREE OF FREEDOM ANALYSIS ABOUT PARALLEL MECHANISM FOR ANKLE REHABILITATION - CHEN GengBiao; YI KuanHan (Jixie qiangdu)
In order to achieve the movement demands of sprained ankle patients in different rehabilitation stages,this paper proposes a kind of metamorphic parallel mechanism for ankle rehabilitation,which can obtain the switch of 3 SPS/PS motion and 3 SPS/S motion by locking or driving the prismatic pair of（ P） S branch chain. The initial configuration of the switch had instantaneously one movement and three rotations in space. Among them,3 SPS/PS configuration has four degrees of freedom,namely the rotation of the moving platform around the x axis,y axis and zaxis and the displacement along the z axis. 3 SPS/S configuration has three degrees of freedom,namely the rotation of the moving platform around the x axis,y axis and z axis,respectively. Finally,the conclusion is verified by screw theory analysis and Adams simulation.